Discovery of a potent and selective inhibitor for human carbonyl reductase 1 from propionate scanning applied to the macrolide zearalenone. - Zimmermann, T; Niesen, F; Pilka, E; Knapp, S; Oppermann, U; Maier, M (2009)
In order to extend the chemical diversity available for organic polyketide synthesis, the concept of propionate scanning was developed. We observed that naturally occurring polyketides frequently comprise not only acetate, but also some propionate as building blocks. Therefore our approach consists of a systematic replacement of some of the acetate building blocks during synthesis by propionate moieties, resulting in additional methyl groups that may give rise to different properties of the polyketides. Here we present the results of a first 'proof of concept' study where a novel zearalenone analogue 5 was prepared that comprises an additional methyl group at C5'. Key steps in the synthesis of 5 include a Marshall-Tamaru reaction, a Suzuki cross-coupling reaction, and a Mitsunobu lactonization. Compared to the parent zearalenone (1), analogue 5 showed reduced binding to a panel of human protein kinases and no binding to human Hsp90. On the other hand, however, 5 turned out to be a potent (IC(50)=210 nM) inhibitor of human carbonyl reductase 1 (CBR1).